2005
DOI: 10.1074/jbc.m509796200
|View full text |Cite
|
Sign up to set email alerts
|

The Docosatriene Protectin D1 Is Produced by TH2 Skewing and Promotes Human T Cell Apoptosis via Lipid Raft Clustering

Abstract: Docosahexaenoic acid, a major -3 fatty acid in human brain, synapses, retina, and other neural tissues, displays beneficial actions in neuronal development, cancer, and inflammatory diseases by mechanisms that remain to be elucidated. In this study we found, using lipid mediator informatics employing liquid chromatography-tandem mass spectrometry, that (10,17S)-docosatriene/neuroprotectin D1, now termed protectin D1 (PD1), is generated from docosahexaenoic acid by T helper type 2-skewed peripheral blood mononu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
194
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(205 citation statements)
references
References 49 publications
10
194
0
1
Order By: Relevance
“…These lipid mediators have been shown to decrease formation of inflammatory cytokines such as TNF␣, IL-6, and others (31,32). Our data confirm decreased levels of cytokines, which may be due to the documented lower NF-B activity in fat-1 mice shown here.…”
Section: Discussionsupporting
confidence: 80%
“…These lipid mediators have been shown to decrease formation of inflammatory cytokines such as TNF␣, IL-6, and others (31,32). Our data confirm decreased levels of cytokines, which may be due to the documented lower NF-B activity in fat-1 mice shown here.…”
Section: Discussionsupporting
confidence: 80%
“…However, they appear to exert their effects through a different set of receptors (75). Several studies have shown that certain members of the resolvin family suppress neutrophil infiltration and cytokine secretion in animal models of inflammation (42,76). Also, they have been shown to be protective following brain injury after experimental stroke (77), for insulin-resistance and hepatic steatosis in obesity (78), airway inflammation (79, 80), and they enhanced wound healing and suppressed colitis (75) in mouse models of inflammatory diseases.…”
Section: Anti-inflammatory Effects Of Lipoxins and Resolvinsmentioning
confidence: 99%
“…One of the pathways for the D-series involves 5-and 15-lipoxygenase activity (42), with evidence that 15-lipoxygenase activity from leukocytes or epithelial cells leads to 17S-hydroxy-DHA (42,43). This has anti-inflammatory effects and can be metabolized further by leukocyte 5-lipoxygenase to the D-series of resolvins or by an epoxydase to the protectins (40,42,44).…”
Section: Biosynthesis Of Resolvins and Protectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, additional pro-inflammatory products have been discovered (Feltenmark et al, 2008). On the other hand, anti-inflammatory and/or pro-resolving lipids generated by mammalian isoforms have also been identified, including lipoxins (Serhan et al, 1984;Maderna & Gordon, 2009), resolvins (Serhan et al, 2004), protectins (Ariel et al, 2005;Schwab et al, 2007) and maresins (Serhan et al, 2009). Therefore, LOX products play important roles in the development of acute inflammation but they have also been implicated in inflammatory resolution.…”
mentioning
confidence: 99%